The Figure of the Musician in German Literature - Schoolfield, George C. (UNC Studies in the Germanic Languages and Literatures, 1956)
This survey of the literary treatment of musicians in German novels and novellas begins with the Romantics and ends with the publication of Thomas Mann's "Doktor Faustus". Schoolfield explores the work of a large selection of writers, including Hoffmann, Tieck, Kleist, Brentano, Grillparzer, Werfel and Hesse among many others. Through these works he tracks the progression of the figure of the musician as professional, artist, genius, composer, and pedagogue and how the pursuit of their art is interpreted by major literary movements.